Exploring the Relation Between Online Case‐Based Discussions and Learning Outcomes in Dental Education. Issue 11 (1st November 2014) - Koole, Sebastiaan; Vervaeke, Stijn; Cosyn, Jan; De Bruyn, Hugo
Abstract : Online case‐based discussions, parallel to theoretical dental education, have been highly valued by students and supervisors. This study investigated the relation between variables of online group discussions and learning outcomes. At Ghent University in Belgium, undergraduate dental students (years two and three) are required to participate in online case‐based discussion groups (five students/group) in conjunction with two theoretical courses on basic periodontics and related therapy. Each week, a patient case is discussed under supervision of a periodontist, who authored the case and performed the treatment. Each case includes treatment history and demand, intra‐ and extraoral images, and full diagnostic information with periodontal and radiographic status. For this retrospective study, data were obtained for all 252 students in forty‐three discussion groups between 2009 and 2012. Spearman's rank correlations were calculated to investigate the relation among group dynamics (number of group posts and views), individual student contributions (number of individual posts, newly introduced elements, questions, and reactions to other posts), supervisors' interventions (number of posts and posed questions), and learning outcomes (examination result). The results showed that learning outcomes were significantly related to the number of student posts (Spearman's rho (ρ)=0.19), newly introduced elements (ρ=0.21), reactions to other posts (ρ=0.14), number of supervisors' interventions (ρ=0.12), and supervisors' questions (ρ=0.20). These results suggest that individual student contributions during online case‐based discussions and the provided supervision were related to learning outcomes.